A near complete genome assembly of chia assists in identification of key fatty acid desaturases in developing seeds - Li, Leiting; Song, Jingjing; Zhang, Meiling; Iqbal, Shahid; Li, Yuanyuan; Zhang, Heng; Zhang, Hui (Frontiers in Plant Science, 2023)
Chia is an annual crop whose seeds have the highest content of α-linolenic acid (ALA) of any plant known to date. We generated a high-quality assembly of the chia genome using circular consensus sequencing (CCS) of PacBio. The assembled six chromosomes are composed of 21 contigs and have a total length of 361.7 Mb. Genome annotation revealed a 53.5% repeat content and 35,850 protein-coding genes. Chia shared a common ancestor with Salvia splendens ~6.1 million years ago. Utilizing the reference genome and two transcriptome datasets, we identified candidate fatty acid desaturases responsible for ALA biosynthesis during chia seed development. Because the seed of S. splendens contains significantly lower proportion of ALA but similar total contents of unsaturated fatty acids, we suggest that strong expression of two ShFAD3 genes are critical for the high ALA content of chia seeds. This genome assembly will serve as a valuable resource for breeding, comparative genomics, and functional genomics studies of chia.